Change in childbearing intention, use of contraception, unwanted pregnancies, and related adverse events during the COVID-19 pandemic: Results from a panel study in rural Burkina Faso. - Thomas Druetz; Sarah Cooper; Frank Bicaba; Alice Bila; Martine Shareck; David-Martin Milot; Cheick Tiendrebeogo; Abel Bicaba (Public Library of Science (PLoS), 2022)
Evidence on how the COVID-19 pandemic has affected women's reproductive health remains scarce, particularly for low- and middle-income countries. Deleterious indirect effects seem likely, particularly on access to contraception and risk of unwanted pregnancies, but rigorous evaluations using quasi-experimental designs are lacking. Taking a diachronic perspective, we aimed to investigate the effects of the pandemic on four indicators of women's reproductive health: history of recent adverse events during pregnancy (past), use of contraception and unwanted pregnancies (present), and childbearing intentions (future). This study was conducted in four rural health districts of Burkina Faso: Banfora, Leo, Sindou and Tenado. Two rounds of household surveys (before and during the pandemic) were conducted in a panel of 696 households using standardized questionnaires. The households were selected using a stratified two-stage random sampling method. All women aged 15-49 years living in the household were eligible for the study. The same households were visited twice, in February 2020 and February 2021. The effects were estimated by fitting hierarchical regression models with fixed effects or random intercepts at the individual level. A total of 814 and 597 women reported being sexually active before and during the COVID-19 pandemic, respectively. The odds of not wanting (any more) children were two times higher during the pandemic than before (2.0, 95% CI [1.32-3.04]). Among those with childbearing intention, the average desired delay until the next pregnancy increased from 28.7 to 32.8 months. When comparing 2021 versus 2020, there was an increase in the adjusted odds ratio of contraception use (1.23, 95% CI [1.08-1.40]), unwanted pregnancies (2.07, 95% CI [1.01-4.25]), and self-reported history of miscarriages, abortions, or stillbirths in the previous 12 months (2.4, 95% CI [1.04-5.43]). Our findings in rural Burkina Faso do not support the predicted detrimental effects of COVID-19 on the use of family planning services in LMICs, but confirm that it negatively affects pregnancy intentions. Use of contraception increased significantly among women in the panel, but arguably not enough to avoid an increase in unwanted pregnancies.